Uso de crowdsourcing e gamificação para motivar a participação e colaboração de cidadãos em sistemas inteligentes de transporte: um estudo de caso com o sistema Antares - Sommer, Tiago (Universidade do Vale do Rio dos Sinos, 2015)
Traffic jams are one of the main problems in the cities. The expansion of urban roads is not a sustainable solution, for this reason other alternatives are necessary. One possible solution are the User Information Systems (UIS). These computer systems aim to provide information about the public transport for users, attracting them to use public transport instead of private vehicles. The main problem of an UIS is to keep its data updated. To solve this problem, we propose an unified model of crowdsourcing and gamification for an UIS. The crowdsourcing aims to allow users to collaborate with updated data. However, only the crowdsourcing may not be enough, because the system will depend on the users participation to keep itself updated. If the users are not motivated to cooperate, the system will downgrade and will no longer be useful. Thus, gamification will be used to motivate users to use the system and also to collaborate with more data. The greater the number of users interested in the system, the better are the chances of getting useful data from users. Likewise, with more information, the system will be more reliable and therefore more users will be interested in using it. The proposed work contains a significative contribution to the Intelligent Transportation Systems area because we are not aware of other studies that integrate gamification and crowdsourcing in an UIS. To verify if the work achieved its objectives, a qualitative evaluation was performed with three users. The users were observed in situ while using the system at bus stops in the city of Porto Alegre. A quantitative experiment evaluation was also conducted in which 23 users watched a video about the system and answered questionnaires with closed questions. The analysis of the users responses showed evidence that they feel motivated to contribute to public transportation. In addition, users also reported to be interested in the gamification of the system.
Keywords: Gamificação; Sistemas inteligentes de transporte; Crowdsourcing; Transporte público; Gamification; Intelligent transport system; Public transport; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação